Mutações do gene SOD-1 (Superóxido Dismutase 1) na forma familiar da esclerose amiotrófica lateral: revisão sistemática - Alves, Aleandro Geraldo (2011)
Amyotrophic lateral sclerosis (ALS) is a multifactorial disease that affects motor neurons. In most cases, the disease is sporadic, however, 5 to 10% of patients have a familial history (FALS). Among patients with FALS, 12 to 23% present with mutations in the SOD1 gene. Objectives: To present a systematic review about the mutations described in SOD1 gene in patients with FALS. Methods: The databases used in this study included PubMed, ISI Web of Science and Cochrane Library Virtual Health. After reading the abstracts, 71 articles were selected and systematically reviewed on this study. Results: The largest number of publications was found in 1997, and Japan was the country with the majority of published studies on the subject, with 23 articles. The majority of the mutations were described in éxons four and five of SOD1 gene, and A4V, I113T, I144F, D90A and L38V were the most commonly mutation described. More than 156 mutations in the SOD1 gene have been cataloged in patients with ALS-F and these data are deposited in ALS GENETICS ONLINE DATABASE, a database that contains specific information on mutations associated with amyotrophic lateral sclerosis. However, the articles reviewed in this study described 103 mutations. Conclusions: Several mutations in the SOD1 gene have been described in patients with ALS-F, however, the relationship between such mutations and the pathogenesis of ALS-F remains unclear, as well as the relationship between mutations and disease progression. Further studies are necessary in order to better explain such relationship.